Efeito das relações bióticas sobre o estabelecimento de macroalgas de ecossistemas lóticos tropicais: interação com microalgas e pressão por herbivoria - Tonetto, Aurélio Fajar [UNESP] (2014)
The stream macroalgae have been considered, along with periphyton, bryophytes and macrophytes, one of the main primary producers in streams environments. For this reason, in recent decades many studies have been performed to understand the spatiotemporal distribution of these organisms. Most of these studies have only investigated the effects of environmental variables on patterns of ecological distribution of macroalgae streams. However, only the relationship between the occurrence and distribution of these organisms and the changes in environment has been shown to be poorly predictive in relation to the establishment and maintenance of macroalgae in these ecosystems. Thus, it seems clear that, beyond the dynamic mosaic of environmental conditions, other forces acting on these organisms should be considered in the analysis of their ecological distributions. In this sense, it is possible to imagine that biotic interactions on a small scale, that occur between coexistent organisms in the same stream stretch can also significantly influence on the ecological responses of these organisms. Microalgae and herbivorous, for example, are organisms that coexist intimately with macroalgae and therefore must have a relevant role in the distribution of these organisms in the environment. In fact, some studies have suggested that the internal factors of community seem to be more important in determining their variations than external, occasional or seasonal factors that act during the period of colonization. In this context, the present study investigated the possible existing biotic interactions between micro and macroalgae in tropical streams, by conducting an experimental study. More specifically, the first objective was to evaluate the existence of competition or cooperation between benthic algae (micro and macroalgae) over a process of colonization on artificial substrates. In addition, we tried to correlate these interactions with the dynamic ...